Recruiting process: agent-get-agent strategy at creative agency MAA Seremban Branch / Faizah Zainal - Zainal, Faizah (Faculty of Business and Management, 2007)
Agent-get-agent is one of the strategies used by Creative Agency in recruiting process. The best sources of recruits are referrals from the successful agents. Chief Consultant has a regular meeting with existing agents on an informal one-to-one basis and discusses who their contacts are and what means to them in terms of recruiting potential. The research objectives are to identify what factors that influence agent to get a new agent, to determine the suitable method in pre-approach for agent to apply during get a new agent, to identify the sources that the agent used to get a new agent. Beside that, researcher wants to make some recommendation in assisting the agency to improve the current strategy in recruiting process.